Study on item analysis of multiple – choice questions amongst the undergraduate dental students (Nepal Medical College Journal, 2023)
Assessments are powerful tools for bringing on the achievement of educational goals and one of the tools for bringing it rightly is “item analysis.” Multiple - Choice Questions (MCQs) are one of the most common methods of assessing the knowledge capabilities of undergraduate and postgraduate medical students. The main objective of this study was to analyze the quality of MCQs and to assess the relationships of items having good difficulty and discrimination indices with their distracter efficiency. After getting an ethical approval from Institutional Review Committee of Nepal Medical College Teaching Hospital a cross – sectional study was conducted over a period of one year from January 2022 to December 2022 in the Department of Human Anatomy of Nepal Medical College. The difficulty index (DIF I), discrimination index (DI) and distracter efficiency (DE) were calculated and analyzed. The results obtained revealed that the mean and standard deviation of DIF I, DI and DE were 56.75±22.6, 0.3±0.2 and 43.24±25.66 respectively. The items analyzed were neither too easy and nor too difficult (DIF I = 62.8%). The majority of items fulfilled the criteria of acceptable difficulty and good discrimination index and the maximum number of items were found to have 2 NFDs (DE = 33.33 %). The present study was hence undertaken as it assists to evaluate the MCQ items to discern its effectiveness in assessing the knowledge of students as well as it plays a vital role in developing a question bank having valid MCQs.